Toxicokinetics of Nanoparticles Deposited in Lungs Using Occupational Exposure Scenarios - Creutzenberg, Otto; Pohlmann, Gerhard; Schaudien, Dirk; Kock, Heiko (Frontiers in Public Health, 2022)
Various synthetic powders with primary particle sizes at nanoscale and a high commercial impact have been studied in inhalation or instillation tests using Wistar rats. The test materials were metal oxides, i.e. TiO2, ZnO and amorphous silica and carbon black (technical soot). Dosing schemes were in the regular ranges typically used to simulate occupational exposure scenarios (mg range). Nanoscaled particle agglomerates have a potential to disintegrate and translocate as individual nanoparticles to remote locations following deposition in lungs. The toxicokinetic fate post-exposure in lungs/organs was investigated for metal oxides i.) by chemical analysis of the retained particulate/dissolved matter and ii.) by visualization of particles in various remote organs using transmission electron microscopy (TEM). For carbon black a radioactive label was selected, i.e. carbon black was tagged internally (“intrinsically”) with a γ tracer (7beryllium; half-time: 53.3 days). Approx. 0.3 mg of the purified test items were intratracheally instilled to lungs of Wistar rats. This dose avoided a particle overload effect, thus, the toxicokinetic fate of carbon black could be followed under physiological conditions of lung clearance. – The three titanium dioxides (NM-103, NM-104, NM-105; JRC coding) showed a very slow dissolution in lung fluids. In contrary, the coated ZnO (NM-111) dissolved quickly and was eliminated from the body within approximately one day. The precipitated amorphous silica (NM-200) showed a partial dissolution. - The chemical analysis in lungs (particulate and soluble TiO2) and in remote organs (liver and brain) showed a small solubility effect under physiological conditions.